Assess the Role of Dental Surgeons in Prevention and Early Diagnosis of Oral Cancers (Medical Forum Monthly, 2024)
ABSTRACTObjective: To determine the role of dentists in early diagnosis and prevention of oral cancers.Study Design: Observational / descriptive study.Place and Duration of Study: This study was conducted at the Islam dental College Hospital, Sialkot and various Dental Clinics in Sialkot region during February and March 2017.Materials and Methods: A questionnaire was designed and distributed among the dentists working in the Islam Dental College hospital as well as in the Sialkot district region to know what role they play in the prevention and early diagnosis of this deadly disease.Results: Only 18% of the dentists thoroughly examined the entire oral mucosa of their patients. More than sixty percents (60%) of the dentists ask about the use of tobacco, alcohol and other risk factors and only 55% advised and helped their patients to quit these habits. Also about 40% dentists did not ask or asked rarely about the use of cancer risk factors. Even fewer 9% considered the possibility and then searched for incidental finding of oral cancer of which only 6% dentists took biopsy or specialist consideration to confirm the finding of suspicious lesions.Conclusion: The results of this study indicate that dental surgeons need to do more for the prevention and early diagnosis of oral cancers.